2019
DOI: 10.1016/j.echo.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Left Ventricular Myocardial Deformation for Left Ventricular Remodeling in Patients With Classical Low-Flow, Low-Gradient Aortic Stenosis Undergoing Transcatheter Aortic Valve Replacement

Abstract: Background: Transcatheter aortic valve replacement (TAVR) is an alternative treatment in surgically intermediate-or high-risk patients with classical low-flow, low-gradient (LFLG) aortic stenosis (AS). The objective of this study was to investigate whether two-dimensional (2D) speckle-tracking echocardiography (STE) can predict left ventricular (LV) flow reserve during dobutamine stress echocardiography (DSE) and remodeling after TAVR in patients with LFLG AS. Methods: Seventy-five symptomatic patients with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Saevik et al ( 22 ) demonstrated safety and feasibility of low-dose dobutamine SE in 50 patients with high gradient AS, showing reduced CR in 40% of them ( 22 ). Finally D’Andrea et al ( 23 ) showed that a cutoff value for left ventricle global longitudinal strain (LV GLS) of >−12% well distinguished patients without significant CR and with lack of positive remodeling after TAVI at follow-up ( 23 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saevik et al ( 22 ) demonstrated safety and feasibility of low-dose dobutamine SE in 50 patients with high gradient AS, showing reduced CR in 40% of them ( 22 ). Finally D’Andrea et al ( 23 ) showed that a cutoff value for left ventricle global longitudinal strain (LV GLS) of >−12% well distinguished patients without significant CR and with lack of positive remodeling after TAVI at follow-up ( 23 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this setting, DSE demonstrated low (≤65%) specificity and sensitivity in predicting it ( 28 ). Finally, left ventricular global longitudinal strain (LVGLS) was analyzed as a parameter useful to predict the presence of CR and the post-TAVI reverse remodeling ( 23 ), showing that a pre-procedural LVGLS > −12% was a strong predictor of pre-procedural CR absence (sensitivity 84%; specificity 93%; AUC 0.92 [95% CI, 0.86–0.99], p < 0.00001) and lack of post-procedural remodeling ( p < 0.0001) ( 23 ). A greater increase in the absolute value of LVGLS after TAVI has been highlighted in patients with pre-procedure CR (+3.9%, p < 0.0001 vs. + 2.3%, p = 0.01) ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, change in GLS correlated with improvement in NYHA class but did not show significant association with major adverse cardiovascular events or 30-day mortality. D'Andrea et al ( 19 ) calculated an LV GLS cutoff of −12.0% to identify LFLG AS patients with lack of remodeling post-TAVR. A recent meta-analysis observed a cutoff of −14.7% as a trigger to consider early interventions ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Другим не менее важным предиктором отдаленной летальности является показатель GLS. В нескольких крупных исследованиях сообщалось, что GLSзначимый фактор риска летальных событий у пациентов с LFLG в отдаленном периоде наблюдения [26,27]. Показатель GLS ЛЖ может быть более чувствительным маркером к изменениям систолической функции ЛЖ, чем ФВ ЛЖ у пациентов c LFLG.…”
Section: Discussionunclassified